Off Beat: Jeff Nuttall and the International Underground: Curating the Counterculture. Issue 1 (1st April 2017) - Field,; Jones,
Abstract : The exhibition Off Beat: Jeff Nuttall and the International Underground (8 September 2016 to 5 March 2017) showcases the archive of Jeff Nuttall (1933–2004), a painter, poet, editor, actor and novelist. As the exhibition illustrates, Nuttall was a central figure in the International Underground during the 1960s through to the early 1970s. During this time he collaborated with a vast network of avant-garde writers from across the globe, as well as editing the influential publication My Own Mag between 1963 and 1967.